Analysis of the Role of Fisherwomen in Managing Marine Tourism in Padak Guar Village, East Lombok Regency - Sulastri, Sulastri; As'urin, Baiq (Jurnal Perikanan dan Kelautan, 2025)
Padak Guar Village is a marine tourism village with great potential. Marine tourism development cannot be separated from the active role of coastal communities, both men and women. Therefore, this research aims to determine the role of female fishermen in managing marine tourism in Padak Guar Village, East Lombok Regency. The method used in this research is descriptive, and data collection is carried out using survey techniques. The results of this research are that the condition of female fishermen in Padak Guar Village, East Lombok Regency, includes: 1) low knowledge of female fishermen about marine tourism villages, 2) low role of female fishermen in managing marine tourism, 3) lack of skills possessed by female fishermen in supporting the progress of marine tourism, 4) Development of female fishermen who have not been involved in managing marine tourism. Increasing the role of women fishermen in managing marine tourism can be done with various programs, including: 1) Socializing the existence of marine tourism, 2) increasing the involvement of women fishermen in managing marine tourism, 3) providing training to women fishermen regarding supporting functions in managing marine tourism, 4) maximizing the role of government and fisheries observers in increasing the institutional capacity of women fishermen